Endocrine side effects during cancer treatment. Lecture for practitioners - Anastasiya A. Glibka; Natalya V. Mazurina; Ekaterina A. Troshina (ZAO "Consilium Medicum", 2022)
Targeted therapy and immune checkpoint inhibitors (ICI) are increasingly being used to treat many solid tumors. The use alpelisib and ICPI has a risk of side-effects, particularly endocrine dysfunctions. In this lecture, there are clearly stated: initial screening, monitoring, selection of therapy and emergency situations for each endocrinopathy, i.e. hyperglycemia during treatment with alpelisib and destructive thyroiditis and hypophysitis during treatment of ICI.